Interaction with Coxsackievirus and Adenovirus Receptor, but Not with Decay-Accelerating Factor (DAF), Induces A-Particle Formation in a DAF-Binding Coxsackievirus B3 Isolate - Milstone, Aaron M. (American Society for Microbiology, 2005)
Although many coxsackie B viruses interact with decay accelerating factor (DAF), attachment to DAF by itself is not sufficient to initiate infection. We examined the early events in infection that follow virus interaction with DAF, and with the coxsackievirus and adenovirus receptor (CAR). Interaction with soluble CAR in a cell-free system, or with CAR on the surfaces of transfected cells, induced the formation of A particles; interaction with soluble or cell surface DAF did not. The results suggest that CAR, but not DAF, is capable of initiating the conformational changes in the viral capsid that lead to release of viral nucleic acid.